Brief Feature of Poverty and Rural poverty and the Circle of Decline in Romanian Rural Area - Cristina Stroe; Cristina Lincaru (Journal of Economic and Social Development (Varaždin), 2022)
In recent years, poverty has become quite important, affecting a large part of the population, which also means driving a sustained effort for specific forms of social assistance. More and more strong signals are being drawn to reduce poverty and social exclusion among vulnerable groups, especially in a rural areas, where the decline in poverty is much more pronounced. This means knowing and continuously analyzing these rural contingencies facing poverty, finding solutions to improve the social assistance system that intensifies the poverty reduction and support social inclusion and employment growth, actions that respond more pronounced in the current economic and social challenges, in line with the dynamics of the social dimensions. This dynamic has multiplied the tensions that social assistance systems have to deal with, thus multiplying the need for adequate, coherent, effective, and efficient social programs. The paper depicts a picture of poverty and the circle of decline in Romania, with particular reference to the rural area that is most affected by poverty. The indicators analyzed in the dynamics suggest that, despite efforts to reduce poverty, even if there have been declines since the beginning of the decade, values remain high, which intensifies the efforts to reduce vulnerabilities and poverty risks faced by a large part of the population, especially in a rural area.